Fundusze unijne dla zrównoważonej turystyki na obszarach Natura 2000 - Zielińska, Anetta (European Union Founds for Sustainable Tourism at Natura 2000 Areas, 2008)
The implementation of sustainable tourism is connected with pro-environmental investments, which require meaningful finances. To achieve the aim it is important to use resources coming from the European Union support, especially those planned for tourism investments at the areas protected by NATURA 2000, such as the European Agricultural Fund for Rural Development, the European Regional Development Fund, the European Social Founds, the Integrated Operational Program for Regional Development. Financing system for NATURA 2000 areas should be precisely presented for building relatively stable economic situation for managers and owners of areas belonging to NATURA 2000. It will make building and functioning at those areas much easier and will get more social acceptance.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 114-123